Bacterial Colonization and Antibiotic Resistance in a Prospective Cohort of Newborn Infants During the First Year of Life. (5th December 2016) - Meropol, Sharon B.; Stange, Kurt C.; Jacobs, Michael R.; Weiss, Judith K.; Bajaksouzian, Saralee; Bonomo, Robert A.
Abstract: Background: Infants are virtually sterile at birth and frequently use antibiotics; our objective was to (1) characterize the longitudinal colonization with bacterial pathogens and associated antibiotic resistance in a cohort of community-dwelling infants in Northeast Ohio and (2) describe longitudinal concurrent antibiotic and daycare exposures. Methods: For 35 newborns, nasopharyngeal swabs were cultured for Streptococcus pneumoniae, anterior nasal for Staphylococcus aureus, and perirectal for extended-spectrum beta-lactamase (ESBL)-producing Gram-negative enteric bacteria, at 3-month intervals for 12 months. Infant and household antibiotics and daycare exposure were assessed longitudinally. Results: Thirteen infants received perinatal or nursery antibiotics. By 3 months, at least 22 were colonized with Gram-negative bacteria; 2 with S pneumoniae (type 19A, resistant; 15C, susceptible), 5 with methicillin-susceptible S aureus. By 12 months, at least 22 of 35 infants received antibiotics, 20 had household members with antibiotics, and 12 attended daycare; 7 more had household members with daycare exposure. The ESBL-producing organisms were not identified. At least 10 infants were colonized at some time with an antibiotic-resistant organism, 3 more with pathogens displaying intermediate resistance. Pathogen colonization and resistance were intermittent and inconsistent. Conclusions: In a community-based cohort followed from birth, early antibiotic and daycare exposures are common, especially considering perinatal maternal exposures. Colonization patterns of Gram-negative bacteria, S pneumoniae, S aureus, and resistant pneumococci are strikingly dynamic. Further research can identify key areas for potential interventions to maximize clinical antibiotic outcomes while minimizing future resistance.